2005
DOI: 10.1111/j.1440-1827.2005.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic granuloma of the oral cavity: Comparative study of its clinicopathological and immunohistochemical features

Abstract: There are two histological types of pyogenic granuloma (PG) of the oral cavity: the lobular capillary hemangioma (LCH) and non-LCH type. The aim of the present study was to examine and compare the clinical features, etiological factors, diameter of vascular elements and immunohistochemical features of LCH and non-LCH histological types of PG to determine whether they are two distinct entities. Thirty cases of LCH and 26 cases of non-LCH PG were retrieved and retrospectively studied. Clinically, LCH PG occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 17 publications
3
85
1
4
Order By: Relevance
“…The color ranges from pink to red to purple depending on the age of the lesion. The surface is characteristically ulcerated and friable 3 . The younger lesions are highly vascular causing considerable bleeding on minor trauma whereas the older lesions become more collagenized and pink.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The color ranges from pink to red to purple depending on the age of the lesion. The surface is characteristically ulcerated and friable 3 . The younger lesions are highly vascular causing considerable bleeding on minor trauma whereas the older lesions become more collagenized and pink.…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly seen in the second decade of life in young adult females. This is perhaps due to the vascular effects of female hormones 2,3 . During pregnancy, the changes in the hormonal levels will exaggerate the response to local irritants.…”
Section: Introductionmentioning
confidence: 99%
“…We carefully reviewed the literature [1][2][3][4][5][6][7] with comparative purposes, taking as bases the main series of cases published by 2010, making up a total of 1,127 cases and, among these, there were only 79 on the tongue -7% of the cases. As far as the etiology is concerned, it has been reported that 80% of the patients with extragingival oral pyogenic granuloma responded positively on local injuries where the lesions appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Among them we stress the pyogenic granuloma (PG) because of its occurrence, typical classical characteristic presentation and distribution in gingival sites in over 80% of the cases [1][2][3][4][5][6][7] . Nonetheless, when extragingival lesions appear, a rare condition listed in the literature, diagnosis may be late [1][2][3][4][5][6][7] . Thus, this paper aims at reporting a case of exuberant pyogenic granuloma in a non-gingival site.…”
Section: Introductionmentioning
confidence: 99%
“…Lip, nasal mucosa, oral mucosa and tongue are the common sites of lobular capillary hemangioma. [19][20] b) A significantly greater number of vessels with perivascular mesenchymal cells non-reactive for alpha-smooth muscle actin and muscle-specific actin are present in the central area of pyogenic granuloma of non-lobular capillary hemangioma variety, compared to lobular capillary hemangioma variety. Lobular capillary hemangioma variety of pyogenic granuloma usually presents as a spontaneous, painless, bleeding mass.…”
Section: Histopathologymentioning
confidence: 99%